PROFESIONALISME APARATUR DESA DALAM MENYELENGGARAKAN PELAYANAN PUBLIK PEMERINTAHAN DESA (STUDI KASUS DI KANTOR DESA JATINOM KABUPATEN BLITAR) - Jihan Sabrina; Sri Umiyat; Wildan Taufik Raharja (Faculty of Social and Political Science, 2020)
Jatinom Village Apparatus organizes the public services in Blitar Regency. This study aims to analyze the professionalism of village officials in the Jatinom village office in Blitar. The research uses qualitative method with a case study approach. Data collection uses observation, interview, documentation with data collection techniques, presentation, condensation, and conclusions. There are four indicators to measure the professionalism of the village apparatus, namely 1) Competence 2) Effectiveness 3) Efficiency 4) Responsible. With six sub indicators, namely Skills, Knowledge, Quantity, Quality, and Time. The results showed that the Professionalism of the Village Apparatus in Organizing Public Services in Jatinom Village Office. There were two professional sub-indicators, namely skills and knowledge. Village officials have good public speaking. However, there are four sub-indicators, namely quantity, quality, time, and responsibility, such as the staffs do not have a set of target time, have different work experiences that affect service quality, and do not obey the working hours.